Seasonal diversity of spiders in a nature reserve from Espinal in Corrientes, Argentina - María Florencia Nadal; Helga Cecilia Achitte-Schmutzler; Ivo Zanone; Pamela Yanina Gonzalez; Gilberto Avalos (Caldasia)
Assessing the spider’s diversity is necessary for the conservation of nature since they play an important role in ecosystems as regulators of insect populations and are good indicators of environmental quality. The reserve contemplated in this study is unique within the Espinal’s plain due to its rocky outcrops, which contain great species diversity, several of them endemic. The objectives of this work were to create an inventory, describe the taxonomic and functional diversity of the Araneae order in the reserve’s forests and grasslands according to the climatic seasons. The samplings were carried out by leaf litter sieving, foliage beating, grassland aspirate and nocturnal direct capture. For each environment, alpha and beta diversity indices were calculated and the abundance distribution model was tested. In total 224 species/morphospecies were identified. Theridiidae was the richest family and the Orbicular Webs Builders guild was the most abundant. Diversity, dominance and equitability indices showed significant differences between warm and cold seasons for forests and grasslands, the distribution of abundance of the species was adjusted to the log-normal distribution model and the similarity of species between seasons did not exceed the 41 %. The results of this study provide preliminary data on the seasonal patterns of Araneae community. New species of spiders are reported for Argentina, many of them with scarce and isolated records in South America, as well as species of ecological importance.*Supplementary material